Plankton distribution, abundance, diversity, and its potential in the tropical man-made lakes of Kenyir and Temenggor in Peninsular Malaysia - FAISAL OTHMAN; AMIRAH YUSLAN; HIDAYU SUHAIMI; NIZALMIE AZANI; ABU HENA MUSTAFA KAMAL; AMIR SHAH RUDDIN M. D. SAH; NADIAH W. RASDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Othman F, Yuslan A, Suhaimi H, Azani N, Kamal AHM, Sah ASRMD, Rasdi NW. 2024. Plankton distribution, abundance, diversity, and its potential in the tropical man-made lakes of Kenyir and Temenggor in Peninsular Malaysia. Biodiversitas 25: 3342-3358. Kenyir and Temenggor Lakes, the largest artificial lakes in Malaysia, are the focus of this study due to their unique ecological characteristics and the limited information available. The study aimed to determine the diversity and abundance of plankton in various habitat ecosystems along Kenyir Lake and Temenggor Lake. The selection of three distinct sampling points, namely sampling point A (coastal zone), sampling point B (lotic zone), and sampling point C (lentic zone), was a strategic decision to ensure a comprehensive representation of the diverse habitat conditions. Samples were collected horizontally using a 30-micrometer-sized plankton net. At Kenyir Lake, thirty-two phytoplankton species were recorded, the major division of phytoplankton, with two hundred twenty-eight individuals belonging to Charophyta (43.75%). For zooplankton, Arthropoda (83.3%) was the highest recorded. At Temenggor Lake, thirty-one species of phytoplankton were recorded. The major division with one hundred sixty-five individuals belonging to Charophyta (32.3%). For zooplankton, the major division with two hundred forty-two individuals belonging to Arthropoda (82.4%). The Shannon diversity index, evenness, and species richness measurements revealed a range of index values due to variation in plankton species due to interaction and habitat conditions. The variation in planktonic abundance in Kenyir Lake and Temenggor Lake was attributed to their habitat preferences due to the freshwater lake's ecosystem's different zones and conditions.